2005
DOI: 10.1007/s10815-005-7481-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal use of fresh and frozen-thawed testicular sperm for intracytoplasmic sperm injection in azoospermic patients

Abstract: The freezing and in vitro culturing of testicular biopsy tissue is a very reliable approach for the management of testicular biopsy specimens from azoospermic patients, and offers the possibility of several treatments of IVF/ICSI from a single sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
7
46
1
Order By: Relevance
“…The fertilization rates achieved with fresh vs. frozen-thawed testicular spermatozoa were 69% vs. 61.7%, the pregnancy rates per embryo transfer were 29.1% vs. 25.0%, and the delivery rates were 85.7% vs. 80.0%, respectively [Rhouma et al 2003]. Wu et al [2005] achieved a fertilization rate of 72% using fresh testicular spermatozoa and 67% using frozen-thawed testicular spermatozoa. A higher proportion of blastocysts have been shown to develop when frozen-thawed spermatozoa are used, compared with fresh spermatozoa [Zorn et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The fertilization rates achieved with fresh vs. frozen-thawed testicular spermatozoa were 69% vs. 61.7%, the pregnancy rates per embryo transfer were 29.1% vs. 25.0%, and the delivery rates were 85.7% vs. 80.0%, respectively [Rhouma et al 2003]. Wu et al [2005] achieved a fertilization rate of 72% using fresh testicular spermatozoa and 67% using frozen-thawed testicular spermatozoa. A higher proportion of blastocysts have been shown to develop when frozen-thawed spermatozoa are used, compared with fresh spermatozoa [Zorn et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…testicular spermatozoa or tissue are reliable approaches for the management of azoospermic patients and could all for the possibility of multiple IVF-ICSI procedures [7]. Previously Park et al [8] reported that acceptable fertilization and pregnancy rates were achieved using frozen testicular spermatozoa as opposed to fresh testicular spermatozoa in obstructive azoospermia (OA).…”
Section: Introductionmentioning
confidence: 99%
“…Although testicular sperm extraction is used frequently to obtain sufficient sperm for ICSI, very few spermatozoa demonstrate twitching motility or are completely immotile in the initial testicular biopsy samples. Our research observed less than 3% motile sperm (slight twitching) during the initial collection of testicular biopsy samples (Wu et al, 2005). In most cases, it is very difficult to find sufficient motile sperm in the initial or frozen-thawed TESE samples.…”
Section: In Vitro Maturation Of Testicular Biopsy Tissuementioning
confidence: 52%
“…Our further experiment showed that after 24 hour in vitro culture, the number of motile sperm increases remarkably, with a maximum motility rate seen between 48-72 hours of culture (Figure 2). Motile spermatozoa still are observed up to 120 hours in culture (Wu et al, 2005). Based on our research and clinical practice, it appears that the optimal time for ICSI using testicular sperm is after 24-48 hours of culture.…”
Section: In Vitro Maturation Of Testicular Biopsy Tissuementioning
confidence: 76%
See 1 more Smart Citation